1979
DOI: 10.1177/014107687907200706
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tourniquet Removal after Knee Replacement

Abstract: This paper describes a prospective trial which was set up in order to decide whether after knee replacement it is better to remove the tourniquet (pneumatic cuff) before closure of the wound or to leave it on until compressive dressings have been applied. In 80 operations studied, there was less blood loss when the tourniquet was removed after closure and bandaging, but there was no difference in wound complications. The only statistically significant difference was attributed to the timing of tourniquet remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 3 publications
(3 reference statements)
1
20
0
3
Order By: Relevance
“…After full texts were assessed for eligibility, 6 studies [11,27–31] were excluded because they were not RCTs, 2 studies were excluded because of different intervention. [32,33] After reviewing bibliographies of each study, 2 studies [12,25] were found. Finally, 16 RCTs [8,10,1225] were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full texts were assessed for eligibility, 6 studies [11,27–31] were excluded because they were not RCTs, 2 studies were excluded because of different intervention. [32,33] After reviewing bibliographies of each study, 2 studies [12,25] were found. Finally, 16 RCTs [8,10,1225] were included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[32,33] After reviewing bibliographies of each study, 2 studies [12,25] were found. Finally, 16 RCTs [8,10,1225] were included in our meta-analysis. The flow chart of study selection is shown in Figure 1 and the characteristics of each study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Wound closure and apposing tissue layers with a firmly applied dressing can produce a local compressive effect and control this bleeding. Comparing different timings of the tourniquet release, significant differences in perioperative blood loss have been found [42][43][44][45][46][47][48][49][50]. A recent meta-analysis by Rama et al [36] found that intraoperative tourniquet release offered a better hemostatic control of major bleeding events that would otherwise have required a reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In total knee replacement surgery, release of the tourniquet before closure of the wound has been recommended to control the divided geniculate branches of the popliteal artery, thereby reducing the blood loss postoperatively (Newman et al 1979, Page et al 1984. Only a few randomized studies have evaluated the efficacy of this procedure, and the results of these studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%